Assessment of the Effect of Satureja montana and Origanum virens Essential Oils on Aspergillus flavus Growth and Aflatoxin Production at Different Water Activities - Marta García-Díaz; Jessica Gil-Serna; Belén Patiño; Esther García-Cela; Naresh Magan; Ángel Medina (Toxins, 2020)
Aflatoxin contamination of foodstuffs poses a serious risk to food security, and it is essential to search for new control methods to prevent these toxins entering the food chain. Several essential oils are able to reduce the growth and mycotoxin biosynthesis of toxigenic species, although their efficiency is strongly influenced by the environmental conditions. In this work, the effectiveness of Satureja montana and Origanum virens essential oils to control Aspergillus flavus growth was evaluated under three water activity levels (0.94, 0.96 and 0.98 aw) using a Bioscreen C, a rapid in vitro spectrophotometric technique. The aflatoxin concentrations at all conditions tested were determined by HPLC-FLD. Aspergillus flavus growth was delayed by both essential oil treatments. However, only S. montana essential oil was able to significantly affect aflatoxin production, although the inhibition percentages widely differed among water activities. The most significant reduction was observed at 0.96 aw, which is coincident with the conditions in which A. flavus reached the highest levels of aflatoxin production. On the contrary, the treatment with S. montana essential oil was not effective in significantly reducing aflatoxin production at 0.94 aw. Therefore, it is important to study the interaction of the new control compounds with environmental factors before their application in food matrices, and in vitro ecophysiological studies are a good option since they provide accurate and rapid results.